Concentric memories, circular encounters, and post-Buddhist imaginations: contesting Dharamsala as ‘Little Lhasa’ - Galván-Álvarez, Enrique (Taylor & Francis Group, 2024)
This paper analyses representations of Dharamsala, Tibetan capital in exile or capital of exiled Tibet, as a pool of signifiers for Tibetan exilic construction. Like Tibetan exile itself, Dharamsala carries the archival claim of preserving everything constructed as authentic about old Tibet. On the other hand, Dharamsala is also regarded as an avant-garde of Tibetan modernity. By focusing on Tenzin Tsundue’s short story ‘Kora. Full Circle’ (2002) and Ritu Sarin and Tenzing Sonam’s film Dreaming Lhasa (2005), I explore various representational trends that expose the inner paradoxes and ambivalences of Tibetan exilic identities at the turn of the twenty-first century. Following Anand’s model of deconstructing and analysing the etymological possibilities of the word Dharamshala, I look at the Tibetan exiled capital as a disputed centre, hosting both nostalgic narratives of reproduction and their very opposite: attempts to reformulate Tibetanness in innovative and disruptive ways.
Keywords: tibetan exile; Dharamsala; circumambulation; film; post-Buddhism; identity; violence